Antifungal Th Immunity: Growing up in Family - Borghi, Monica; Renga, Giorgia; Puccetti, Matteo; Oikonomou, Vasileios; Palmieri, Melissa; Galosi, Claudia; Bartoli, Andrea; Romani, Luigina (Frontiers in Immunology, 2014)
Fungal diseases represent an important paradigm in immunology since they can result from either the lack of recognition or over–activation of the inflammatory response. Current understanding of the pathophysiology underlying fungal infections and diseases highlights the multiple cell populations and cell-signaling pathways involved in these conditions. A systems biology approach that integrates investigations of immunity at the systems-level is required to generate novel insights into this complexity and to decipher the dynamics of the host–fungus interaction. It is becoming clear that a three-way interaction between the host, microbiota and fungi, dictates the types of host-fungus relationship. Tryptophan metabolism helps support this interaction, being exploited by the mammalian host and commensals to increase fitness in response to fungi via resistance and tolerance mechanisms of antifungal immunity. The cellular and molecular mechanisms that provides immune homeostasis with the fungal biota and its possible rupture in fungal infections and diseases will be discussed within the expanding role of antifungal Th cell responses.